Características agronômicas e tecnológicas de genótipos de feijão do grupo comercial Carioca - Lemos, Leandro Borges; Oliveira, Ricardo Soares de; Palomino, Edwin Camacho; Silva, Tiago Roque Benetoli da (FapUNIFESP (SciELO), 2004)
Cultivars with high yield, adaptability and desirable technological characteristics are a must. The objective of this work was to evaluate agronomic and technologic characters of common bean genotypes from carioca commercial group. Genotypes were cultivated in water growing season, in 2001 and 2002. The experimental design was by randomized blocks with 29 genotypes and four replications. The IAC-Carioca, FT-Bonito, Rudá, Porto Real, CNFC 8008, CNFC 8011, CNFC 8012, CNFC 8013 and CNFC 8156 genotypes yielded above the average. The genotypes IAC-Carioca, CNFC 8012 and CNFC 8156 presented the best results with 3,000 kg ha-1 and 20 minutes cooking time.

A busca por cultivares produtivas, adaptadas ao local de cultivo e com características tecnológicas desejáveis é uma constante. O objetivo deste trabalho foi avaliar o comportamento de genótipos de feijão, do grupo comercial Carioca, quanto a características agronômicas e tecnológicas. Vinte e nove genótipos foram cultivados na época das águas, nos anos de 2001 e 2002, e distribuídos em blocos casualizados, com quatro repetições. Sobressaíram-se os genótipos IAC-Carioca, FT-Bonito, Rudá, Porto Real, CNFC 8008, CNFC 8011, CNFC 8012, CNFC 8013 e CNFC 8156 com produtividade de grãos acima da média obtida. Destacaram-se com produtividade média de grãos acima de 3.000 kg ha-1 e tempo de cozimento médio em torno de 20 minutos, os genótipos IAC-Carioca, CNFC 8012 e CNFC 8156.
Agronomic and technologic characteristics of common bean genotypes from Carioca commercial group
Keywords: Crude protein; Grain hydration; Phaseolus vulgaris; Production components; Yield; Katsuwonus pelamis; Phaseolus (angiosperm)